Unraveling the power of peptides from Cucumaria frondosa coelomic fluid as multitarget therapy of diabetic kidney disease: An in-silico study - Rita, Rauza S.; Cuandra, Kevin N.; Nasri, Syahidatul A.; Carmenita, Mutiara A.; Kristaningtyas, Nathania A.; Rasendriya, Daffa Z.; Maulana, Rafi; Hibatullah, Muhammad N.; Yahono, Angela S.; Afdhal, Fitrah; Ibrahim, Filzatuz Z.; Nayu, Balqist K.; Teguh, Muhammad (Narra J, 2025)
Diabetic kidney disease is a condition characterized by persistent albuminuria, diabetic glomerular lesions, and a reduced glomerular filtration rate in people with diabetes. Peptides in Cucumaria frondosa coelomic fluid have been proven to provide antidiabetic and anti-inflammatory activity that can be used as one of the innovations in developing a multitarget therapy, especially in diabetic kidney disease. Therefore, the aim of this study was to unravel the power of peptide-based metabolites from C. frondosa coelomic fluid as multitarget therapy for diabetic kidney disease using an in-silico study. UCSF Chimera software was utilized to construct the three-dimensional structure of coelomic fluid peptides from C. frondosa. The toxicity and allergenicity of peptides were examined using the ToxinPred and AllerTop websites, respectively. From the PDBJ database, the 3D structures of protein kinase B, alpha isoform (AKT1); vascular endothelial growth factor receptor 2 (VEGFR2); epidermal growth factor receptor (EGFR); α-glucosidase; and glucokinase were obtained. Molecular docking was carried out using MOE Software. In this in-silico study, peptide 9 (-10.32 kcal/mol), peptide 1 (-9.41 kcal/mol), and peptide 3 (-9.55 kcal/mol) were shown to act as specific adenosine triphosphate-competitive inhibitors of EGFR, AKT1, and VEGFR2, respectively. Peptide 8 (-11.06 kcal/mol) can specifically inhibit α-glucosidase by binding to its active site. Peptide 1 (-9.80 kcal/mol) is predicted to specifically inhibit glucokinase activity by blocking its active side. Molecular dynamics simulations confirmed stable interactions with receptor proteins. In conclusion, C. frondosa coelomic fluid peptides have been shown not only to alleviate diabetic kidney disease but also to stabilize blood glucose levels and prevent hyperglycemia based on in-silico analysis.